Pseudospectral Method Based on Müntz–Legendre Wavelets for Solving the Abel Integral Equation - Ioannis Dassios; Fairouz Tchier; F. M. O. Tawfiq (Journal of Mathematics)
This paper deals with the numerical solution of the Abel integral equation based on Müntz–Legendre wavelets. To this end, the Abel integral operator is represented by Müntz–Legendre wavelets as an operational matrix. To find this matrix, we use the similarity between the Abel integral operator and the fractional integral operator. The proposed method can be easily used to solve weakly singular Volterra integral equations. We have proved the convergence of the proposed method. To demonstrate the ability and accuracy of the method, some numerical examples are presented.